CAPABILITIES OF VIDEO-ASSISTED LAPAROSCOPY IN THE DIAGNOSIS AND TREATMENT OF PERFORATION OF THE SMALL INTESTINE AND MECKEL’S DIVERTICULUM (2 CLINICAL OBSERVATIONS) - I. I. Kirsanov; T. P. Makedonskaya; S. A. Tarasov; P. A. Yartsev (Неотложная медицинская помощь)
BACKGROUND Misdiagnosis of acute appendicitis reaches 40%. Video laparoscopy allows the correct diagnosis to be establishedin 98.1%, and identify the other disease excluding the initial diagnosisin 1.6%, as well as to determine the optimal surgical approach and perform minimally invasive surgery, if possible.MATERIAL Clinical observation of 2 cases of perforation of the small intestine.CONCLUSION The use of laparoscopy in acute surgical disease of abdominal organs allows to establish the correct diagnosis and properly provide a therapy with a minimal surgical trauma.